The Economic Costs of Child Maltreatment in UK - Gabriella Conti; Elena Pizzo; Stephen Morris; Mariya Melnychuk (Institute of Labor Economics (IZA), 2021)
Child maltreatment is a major public health problem with significant consequences for individual victims and for society. In this paper we quantify for the first time the economic costs of fatal and non-fatal child maltreatment in the UK in relation to several short-, medium- and long-term outcomes ranging from physical and mental health problems, to labour market outcomes and welfare use. We combine novel regression analysis of rich data from the National Child Development Study and the English Longitudinal Study of Ageing with secondary evidence to produce an incidence-based estimate of the lifetime costs of child maltreatment from a societal perspective. The discounted average lifetime incidence cost of non-fatal child maltreatment by a primary caregiver is estimated at Â89,390 (95% uncertainty interval Â44,896 to Â145,508); the largest contributors to this are costs from social care, short-term health and long-term labour market outcomes. The discounted lifetime cost per death from child maltreatment is estimated at Â940,758, comprising health care and lost productivity costs. Our estimates provide the first comprehensive benchmark to quantify the costs of child maltreatment in the UK and the benefits of interventions aimed at reducing or preventing it.
Keywords: I18; J17; D61; 330; productivity losses; health care costs; lifetime costs; incidence-based approach; child maltreatment; sensitivity analysis